First breeding of lesser kestrel Falco naumanni in Campania (Avocetta, 2025)
The Lesser Kestrel (Falco naumanni) is a small falcon whose Italian breeding range is currently expanding. Summer records from Campania have been considered to refer to wandering individuals from breeding colonies in nearby Puglia and Basilicata. This short communication describes the first documented breeding record in Campania, from a farmland area on the coastal plain of Caserta province. The pair nested successfully with at least one fledged juvenile; the date of fledging, at the end of July, is about one month later than typical fledging dates elsewhere in Italy.
Keywords: lesser kestrel; nesting; breeding; rural areas